A Comparative Analysis of Stock Brokers in India: A comprehensive study of stock brokers in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The stock exchange is the barometer of the economy. The growth and development of an economy depends on the smooth functioning of the stock exchange. The stock exchanges mobilize the savings and give an opportunity to the public to invest their surplus funds in the most profitable ventures. The stock brokers play an important role in the stock exchange. A stock broker is an individual who is professionally regulated by the stock exchange and also associated with the brokerage firm, does the work of buying and selling securities through stock exchange on behalf of retail as well as institutional investors in return for a commission or fees. In our study, we made a comparative analysis of different stock brokers in India.